Taste Receptor Cells Generate Oscillating Receptor Potentials by Activating G Protein-Coupled Taste Receptors - Nakao, Yoshiki; Tateno, Katsumi; Ohtubo, Yoshitaka (Frontiers in Physiology, 2022)
The receptor potentials of taste receptor cells remain unclear. Here, we demonstrate that taste receptor cells generate oscillating depolarization (n = 7) with action potentials in response to sweet, bitter, umami, and salty taste substances. At a lower concentration of taste substances, taste receptor cells exhibited oscillations in membrane potentials with a low frequency and small magnitude of depolarization. Although the respective waves contained no or 1–2 action potentials, the taste receptor cells generated action potentials continuously in the presence of taste stimuli. Both the frequency and magnitude of oscillations increased when the concentration was increased, to 0.67–1.43 Hz (n = 3) and Δ39–53 mV (n = 3) in magnitude from −64.7 ± 4.2 to −18.7 ± 5.9 mV, which may activate the ATP-permeable ion channels. In contrast, a sour tastant (10-mM HCl) induced membrane depolarization (Δ19.4 ± 9.5 mV, n = 4) with action potentials in type III taste receptor cells. Interestingly, NaCl (1 M) taste stimuli induced oscillation (n = 2) or depolarization (Δ10.5 ± 5.7 mV at the tonic component, n = 9). Our results indicate that the frequency and magnitude of oscillations increased with increasing taste substance concentrations. These parameters may contribute to the expression of taste “thickness.”